STUDY OF THE AWARENESS AND READINESS TO ACT IN DISASTERS OF FOREIGN CITIZENS TEMPORARILY RESIDING IN THE CITY OF PLEVEN - Rositza Vasileva; Anton Georgiev; Penka Kostadinova (Peytchinski Publishing, 2023)
According to official data from EM-DAT (the International Disaster Database for Disaster Epidemiology) in 2021, the number of catastrophic events related to natural disasters worldwide was 432, exceeding the average annual number of 347 from 2001 - 2020. In this context, a study involving 240 citizens from 31 different countries who were temporarily residing in the city of Pleven was conducted. This study aimed to gauge their willingness to take adequate action and provide medical assistance in various disasters. All foreign citizens temporarily residing in Pleven had experienced a disaster situation, with over half having experienced more than one. However, the awareness among these two analyzed groups about potential disaster threats was found to be very low. Our study revealed low awareness and a lack of willingness to act during disasters. Only 20% were familiar with early warning sirens; more than half did not have home or property insurance; 88% did not possess an evacuation backpack; and only 15% were knowledgeable about collective remedies. The study's results highlight the need for systematic, in-depth work from responsible institutions to prepare foreigners for potential disasters and accidents.